2010
DOI: 10.1104/pp.110.156224
|View full text |Cite
|
Sign up to set email alerts
|

Tyloses and Phenolic Deposits in Xylem Vessels Impede Water Transport in Low-Lignin Transgenic Poplars: A Study by Cryo-Fluorescence Microscopy    

Abstract: Of 14 transgenic poplar genotypes (Populus tremula 3 Populus alba) with antisense 4-coumarate:coenzyme A ligase that were grown in the field for 2 years, five that had substantial lignin reductions also had greatly reduced xylem-specific conductivity compared with that of control trees and those transgenic events with small reductions in lignin. For the two events with the lowest xylem lignin contents (greater than 40% reduction), we used light microscopy methods and acid fuchsin dye ascent studies to clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 101 publications
4
85
0
1
Order By: Relevance
“…S7), as was previously noticed in greenhouse-grown CCR-downregulated poplars (13). In 4CL-down-regulated poplar, the reduced growth has been attributed to collapsed xylem and the formation of tyloses in the vascular system, and it was shown that vascular tissue in the red areas is defective in its transport capacity (22,28). One option to circumvent the negative consequences of lignin down-regulation on plant performance while still achieving strong down-regulation is to specifically target the down-regulation to fibers but leaving the vessels intact.…”
Section: Discussionsupporting
confidence: 54%
“…S7), as was previously noticed in greenhouse-grown CCR-downregulated poplars (13). In 4CL-down-regulated poplar, the reduced growth has been attributed to collapsed xylem and the formation of tyloses in the vascular system, and it was shown that vascular tissue in the red areas is defective in its transport capacity (22,28). One option to circumvent the negative consequences of lignin down-regulation on plant performance while still achieving strong down-regulation is to specifically target the down-regulation to fibers but leaving the vessels intact.…”
Section: Discussionsupporting
confidence: 54%
“…Lignin in stems and root cell walls promote greater resistance to embolism, a phenomenon associated with death of woody plants under severe conditions of water deficit and winds capable of raising water pressure in xylem vessels resulting in increased transpiration rate (RETUERTO; WOODWARD, 1993;MARTÍNEZ-VILALTA;PIÑOL, 2003;KITIN et al, 2010). Therefore, the value of the partial correlation coefficient between lignin content of seedling root system with survival (r = 0.98) can also be associated with the maintenance of hydraulic conductivity in the xylem.…”
Section: Discussionmentioning
confidence: 99%
“…2, F and L). Extensive anatomical investigations of lowlignin poplar wood (Kitin et al, 2010) suggest that this partial collapse can be caused by slide preparation or partial recovery of cells that were almost completely collapsed before preparation. In either case, the cell wall material was apparently weaker.…”
Section: Lignin Content Was Inversely Associated With Xylem Deformationmentioning
confidence: 99%